Advanced energy architectural configurations and its influence on the indoor environment in various climatic regions. Issue 1 (1st January 2018) - Alwetaishi, Mamdooh
Abstract: One of the most important functions of buildings is to provide comfort with minimum reliance on energy consumption. Many research focuses on the physical part of the building, which has resulted in a lack of investigation considering design and configuration. After the announcement of the Saudi vision of 2030, which aims to improve building performance, the aim of this research is to investigate the influence of models and sub-models of complex architectural configurations in various climatic regions. This will not only have its impact in the kingdom of Saudi, but it will also benefit users and institutions globally. These models have not been investigated before in terms of energy performance and thermal comfort, which makes this research highly essential. The research will use TAS EDSL modelling, which is considered as one of the most powerful and advanced tools for predicting buildings' energy performances. It can be seen that in all regions, the relationship between the indoor temperature and relative humidity has an inverse pattern. Having high relative humidity will make it difficult to achieve indoor comfort temperatures levels for the users with higher indoor air temperatures. This might require an increase in the indoor air velocity by natural pressure or even by mechanical means, such as fans. It will be concluded that linear and radial shapes are not recommended for extreme regions, whether they be hot or cold.